Myriophyllum brasiliense Camb., an aquarium plant in natural waters in Hungary - Illyés, Zoltán; Tóth, Eszter; Magos, Gábor; Tóth, Zoltán (JOURNAL OF LANDSCAPE ECOLOGY, 2006)
The aquatic weed Myriophyllum brasiliense Camb., native to tropical and subtropical South America, have been detected recently in two natural water bodies in Hungary. This reed-grass is widely used indoor as an aquarium plant, but was not yet sighted in the field. Now it was observed in warm-water sections of two different streams. A warm-water spring prevents the winter freezing of the Kácsi-patak along a few-kilometer section, while the Tarnóca-patak receives warm interstitial water, and thus is similarly heated in certain parts. In 2005 and 2006 we monitored the persistence of M. brasiliense populations in these two habitats, checked water temperature changes, recorded the phytocoenological status of the plant and preliminary molecular taxonomic studies were also done. Molecular taxonomic and morphological data obtained so far congruently indicate two independent escapes of M. brasiliense, and in the Kácsi-patak suggest possible hybridization with the sympatric native M. verticillatum.
Keywords: Myriophyllum brasiliense; Kácsi-patak; Tarnóca-patak; ITS sequences